Behavior of the real estate market. Case of apartments in Barquisimeto, Lara State – period 2005-2011 (Gaceta Técnica, 2015)
This article presents a descriptive study about the behavior of the real estate market, specifically the case of apartments in Barquisimeto, Lara state – period 2005-2011. The electronic calculation sheet and a statistical program were used to the automatic processing of the data. The data considered were: location, area (m2), unit price, number of purchase-sale transactions, sale amounts, among others. An econometric model is presented as part of the results. Such model is used to the estimation of unit price of the apartments. The explanatory variables of the model were generated from 3.319 purchase- sale transactions done during the study under period. The obtained information allows a better understanding of the dynamic, the structure and the profile of the local real estate market. All of them provide a perspective of the sector’s current situation under study
Keywords: real estate market; apartments; price estimation; Barquisimeto